The performativity thesis and the interactions between economic theories and social reality - Neris Junior, Celso Pereira [UNESP]; Fucidji, José Ricardo; de Almeida, Rafael Galvão (FapUNIFESP (SciELO), 2021)
Originally proposed by philosopher of language John Austin, and later adapted by other social sciences, the performativity thesis has been known as a critique of the homo economicus of mainstream economics. The performativity of economics is the idea that economics gives birth to activities and markets in the economy (rather than merely describe or interpret them). This paper re-views arguments for and against performa-tivity as a useful way of thinking about the economics-economy relationship. Following this survey, we put forward our interpreta-tion, viz., an interactive approach to this subject. By doing so, we argue for its episte-mological relevance for economic methodol-ogy, i.e., for understanding the relationship between theories and economic models and the events in the economy. Furthermore, we claim that because they are embedded in social reality, mainstream economic theories occupy a particularly resilient position.
A tese da performatividade e as interações entre teorias econômicas e realidade social
Keywords: Economic theory; Performativ-ity of economics; Social reality